2020
DOI: 10.1080/19490976.2020.1758008
|View full text |Cite
|
Sign up to set email alerts
|

Host–microbiome interactions: the aryl hydrocarbon receptor as a critical node in tryptophan metabolites to brain signaling

Abstract: Tryptophan (Trp) is not only a nutrient enhancer but also has systemic effects. Trp metabolites signaling through the well-known aryl hydrocarbon receptor (AhR) constitute the interface of microbiome-gut-brain axis. However, the pathway through which Trp metabolites affect central nervous system (CNS) function have not been fully elucidated. AhR participates in a broad variety of physiological and pathological processes that also highly relevant to intestinal homeostasis and CNS diseases. Via the AhR-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 129 publications
(157 reference statements)
2
57
0
Order By: Relevance
“…The abnormal 5-HT synthesis caused by intestinal dysbiosis could affect the pathological process of AD [ 41 ]. In addition, the well-known AhR signaling of tryptophan metabolites constituting the interface of microbiota–gut–brain axes [ 42 ], could suppress pro-inflammatory cytokines in astrocytes [ 43 ] and microglia [ 42 ], and has the potential to participate in several brain diseases including AD [ 42 ]. Consistent with the reported tryptophan metabolites in human CSF [ 16 ], our findings added evidence that fecal tryptophan metabolism might be under the control of microbiota and the crosstalk of microbiota–host might play a role in the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abnormal 5-HT synthesis caused by intestinal dysbiosis could affect the pathological process of AD [ 41 ]. In addition, the well-known AhR signaling of tryptophan metabolites constituting the interface of microbiota–gut–brain axes [ 42 ], could suppress pro-inflammatory cytokines in astrocytes [ 43 ] and microglia [ 42 ], and has the potential to participate in several brain diseases including AD [ 42 ]. Consistent with the reported tryptophan metabolites in human CSF [ 16 ], our findings added evidence that fecal tryptophan metabolism might be under the control of microbiota and the crosstalk of microbiota–host might play a role in the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, fecal IPYA could classify AD and aMCI from normal cognitive HC. IPYA is one of the major precursor metabolites that can be converted into numerous AhR ligands [ 42 ]. However, we did not find coordinately enriched AhR ligands in the intestine of AD patients, suggesting that the metabolic conversion of IPYA to AhR ligands was suppressed in aMCI and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the expression of IDO/TDO is regulated by activation of AHR; 109 , 110 tryptophan catabolites via kynurenine pathway are involved in immune, metabolic and neural communication mechanisms in gut-brain axis, which is controlled by AHR activation. 111 In addition, certain microbiota that produce indole and indole derivatives from dietary tryptophan can also control astrocyte activity to influence CNS inflammation. 112 Another study reported AHR agonists in serum are altered during different stages of multiple sclerosis, 113 the most common neurological autoimmune disease of CNS.…”
Section: Ahr and Central Nervous Systemmentioning
confidence: 99%
“…IBD is induced by the dysbiosis of gut microbiome, consisted of CD and ulcerative colitis (UC). In the process of ameliorating intestinal inflammation, AHR is mainly protective node in IBD 170,171 . Indole and most of its derivatives are agonists or antagonists of AHR.…”
Section: Microbial Metabolites As Potential Targets For Controlling Imentioning
confidence: 99%